First record of Viannaiidae (Nematoda: Trichostrongylina) in fossorial rodents (Ctenomys spp.) from Central Argentina, with description of a new genus and species - Serrano, Paula Carolina; Digiani, María Celina (Zootaxa, 2016)
A new genus and species of Viannaiidae (Trichostrongylina, Heligmosomoidea), Ischilinema baldoi n. gen. et sp. is described parasitizing two species of tuco-tucos, Ctenomys bergi and Ctenomys rosendopascuali (Rodentia, Hystricomorpha, Ctenomyidae) from Córdoba province, Central Argentina. No helminths were previously known from these two host species. The new genus is defined by the following characters: synlophe with 15 continuous ridges subequal in size, presence of left cuticular dilatation, a gap between ridges 1’ and 2’, bursa asymmetrical with dorsal ray hypertrophied and displaced to the right, and spicules not twisted. This is the first record of Viannaiidae from the Ctenomyidae, enlarging the host range of these parasites to five out of the 12 extant families of caviomorphs.